Liberal Illiberalism? The Reshaping of the Contemporary Populist Radical Right in Northern Europe - Moffitt, Benjamin (2017)
Populism, particularly in its radical right-wing variants, is often posited as antithetical to the principles of liberalism. Yet a number of contemporary cases of populist radical right parties from Northern Europe complicate this characterisation of populism: rather than being directly opposed to liberalism, these parties selectively reconfigure traditionally liberal defences of discriminated-against groups—such as homosexuals or women—in their own image, positing these groups as part of ‘the people’ who must be protected, and presenting themselves as defenders of liberty, free speech and ‘Enlightenment values’. This article examines this situation, and argues that that while populist radical right parties in Northern Europe may only invoke such liberal values to opportunistically attack their enemies—in many of these cases, Muslims and ‘the elite’ who allegedly are abetting the ‘Islamisation’ of Europe’—this discursive shift represents a move towards a ‘liberal illiberalism’. Drawing on party manifestoes and press materials, it outlines the ways in which these actors articulate liberal illiberalism, the reasons they do so, and the ramifications of this shift.